LEGAL DYNAMICS AND IMPLEMENTATION PROBLEMS OF JUDICIAL REVIEW AUTHORITY IN THE SUPREME COURT - Janpatar Simamora (Jurnal Dinamika Hukum, 2016)
This paper is intended to find out how the development of settings as well as problems of imple-mentation of judicial review authority of the Supreme Court. Based on the development the settings, the Supreme Court has long had the judicial review authority. Correspondingly, there is a develop-ment setting judicial review authority through a number of regulations. However, in practice, there are a number of problems. First, in terms of regulation, not reflecting the comprehensive procedu-ral law. Second, in terms of judicial review case handling process, has not shown that there is trans-parency. Therefore, it should be repair, so that the implementation of such authorities take place optimally and able to offset the reputation of the Court. Keywords: judicial review, judicial institutions, Supreme Court